Evidence-based medicine - Heppner, Hans Jürgen; Singler, Katrin; Sieber, Cornel; Christ, M.; Heirler, F.; Schoenhofer, B. (Zeitschrift für Gerontologie und Geriatrie, 2011)
The demographic shift means that there are an increasing number of elderly critically ill patients with various comorbidities. This very specific group needs particular treatment which has not been considered sufficiently in medical guidelines so far. To improve health care, it is indispensable not only to work out the current guidelines, but aspects of geriatric medicine must also be integrated into future developments. Using the example of the recent guideline "non-invasive ventilation," it is shown how the process of designing and implication can actively be realized in clinical daily routine.
Keywords: Respiration; artificial; Critical care; Practice guidelines as topic; Elderly; Geriatrics